SKETCHING HISTORICAL CONTEXT IN LEE DANIEL'S 'THE BUTLER': A MIMETIC APPROACH - Harang, Heronimus; Engliana, Engliana; Supadi, Supadi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2019)
The purpose of this research is to analyze Daniels’ work of historical context in his movie The Butler. To reveal the purpose of research, the writers utilize qualitative methodology with a mimetic approach to analyze the historical context in the movie. The results concluded that this movie gives a significant proportion in three types of history, namely political, social, and intellectual history. In the political aspect, the movie depicts the history when the United States used to establish the Segregation Law based on racial background. In the social aspect, the movie depicts non-white Americans who were considered unworthy. Whereas, in intellectual aspect, the movie portrays many historical figures and other Americans who fought the injustice demanding equality as the citizens.